Biomechanical changes and recovery of gait function after total hip arthroplasty for osteoarthritis: a systematic review and meta-analysis. Issue 7 (July 2018) - Bahl, J.S.; Nelson, M.J.; Taylor, M.; Solomon, L.B.; Arnold, J.B.; Thewlis, D.
Summary: Objective: To determine the change in walking gait biomechanics after total hip arthroplasty (THA) for osteoarthritis (OA) compared to the pre-operative gait status, and to compare the recovery of gait following THA with healthy individuals. Methods: Systematic review with meta-analysis of studies investigating changes in gait biomechanics after THA compared to (1) preoperative levels and (2) healthy individuals. Data were pooled at commonly reported time points and standardised mean differences (SMDs) were calculated in meta-analyses for spatiotemporal, kinematic and kinetic parameters. Results: Seventy-four studies with a total of 2, 477 patients were included. At 6 weeks postoperative, increases were evident for walking speed ( SMD : 0.32, 95% confidence intervals (CI) 0.14, 0.50), stride length ( SMD : 0.40, 95% CI 0.19, 0.61), step length ( SMD : 0.41, 95% CI 0.23, 0.59), and transverse plane hip range of motion (ROM) ( SMD : 0.36, 95% CI 0.05, 0.67) compared to pre-operative gait. Sagittal, coronal and transverse hip ROM was significantly increased at 3 months ( SMDs : 0.50 to 1.07). At 12 months postoperative, patients demonstrated deficits compared with healthy individuals for walking speed ( SMD : −0.59, 95% CI −1.08 to −0.11), stride length ( SMD : −1.27, 95% CI -1.63, −0.91), single limb support time ( SMD : −0.82, 95% CI −1.23, −0.41) and sagittal plane hip ROM ( SMD : −1.16, 95% CI −1.83, −0.49). Risk of bias scores ranged from seven to 24 out of 26. Conclusions: Following THA for OA, early improvements were demonstrated for spatiotemporal and kinematic gait patterns compared to the pre-operative levels. Deficits were still observed in THA patients compared to healthy individuals at 12 months.